Effects of different compost amendments on the abundance and composition of alkB harboring bacterial communities in a soil under industrial use contaminated with hydrocarbons - Schloter, Michael (Frontiers in Microbiology, 2014)
Alkane degrading microorganisms play an important role for the bioremediation of petrogenic contaminated environments. In this study, we investigated the effects of compost addition on the abundance and diversity of bacteria harboring the alkane monooxygenase gene (alkB) in an oil-contaminated soil originated from an industrial zone in Celje, Slovenia (Technosol). Soil without any amendments (control soil) and soil amended with two composts differing in their maturation stage and nutrient availability, were incubated under controlled conditions in a microcosm experiment and sampled after 0, 6, 12, and 36 weeks of incubation. As expected the addition of compost stimulated the degradation of alkanes in the investigated soil shortly after the addition. By using quantitative real-time PCR higher number of alkB genes were detected in soil samples amended with compost compared to the control soils. To get an insight into the composition of alkB harboring microbial communities, we performed next generation sequencing of amplicons of alkB gene fragment. Richness and diversity of alkB gene harboring prokaryotes was higher in soil mixed with compost compared to control soils with stronger effects of the less maturated, nutrient poor compost. The phylogenetic analysis of communities suggested that the addition of compost stimulated the abundance of alkB harboring Actinobacteria during the experiment independent from the maturation stage of the compost. AlkB harboring γ-proteobacteria like Shewanella or Hydrocarboniphaga as well as α-proteobacteria of the genus Agrobacterium responded also positively to the addition of compost to soil. The amendment of the less maturated, nutrient poor compost resulted in addition in a large increase of alkB harboring bacteria of the Cytophaga group (Microscilla) mainly at the early sampling time points. Our data indicates that compost amendments significantly change abundance and diversity pattern of alkB harboring microbes in Technosol and might be a useful agent to stimulate bioremediation of hydrocarbons in contaminated soils.